Clinical Applications of Metronomic Chemotherapy - Bocci, Guido; Francia, Giulio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Metronomic chemotherapy is now, finally, in clinical use. After 20 years of preclinical development and clinical trials, the emerging data will be of paramount importance in allowing us to assess the impact of metronomic chemotherapy on different tumor types. Indeed, it is likely that the next decade will see a major reassessment of the possible applications of metronomic chemotherapy, both alone and in combination with new therapeutic approaches such as immunotherapies, for the management of cancer. Moreover, the results of clinical trials will likely profoundly affect the direction of the laboratory efforts that are going on in parallel and aiming to improve the personalization of this therapeutic strategy. This Special Issue is our attempt to cover the past and present clinical results that have brought us to this pivotal moment and will form the basis of future clinical developments. Scientists and clinicians caring for cancer patients are well aware of the challenges in dealing with this particular therapeutic approach; one such challenge is obtaining improvements in patient survival without significant toxicity. This edition includes clinical research on chemotherapy and ongoing controversies related to metronomic chemotherapy.